Kontribusi Kegiatan Pramuka terhadap Pembentukan Akhlak Siswa dalam Perspektif Pendidikan Islam: Studi Literatur - Wahid, Abd; Ridwan, Ridwan; Saifuddin, Saifuddin (UI DDI AGH AD Polewali Mandar, 2025)
This study aims to examine the contribution of Scout activities in shaping students' moral character from the perspective of Islamic education through a literature review. The method applied is descriptive qualitative with a library research approach, analyzing accredited national journals and repositories from Islamic education institutions. The results indicate that Scout activities play a significant role in the internalization of Islamic values such as honesty, responsibility, tolerance, and cooperation. Activities such as camping, community service, and leadership training serve as effective moral development platforms aligned with Islamic educational principles. Scout programs bridge formal and non-formal education by integrating spiritual, social, and emotional elements in character formation. The study concludes that Scout activities are highly relevant in supporting the vision of Islamic education focused on nurturing morally upright individuals.